Giving birth to the impossible: theology and deconstruction in Johannes Climacus’s Philosophical Fragments - Middleton, T (Taylor and Francis, 2021)
According to Roger Poole, theological interpreters of Søren Kierkegaard’s indirect communication privilege content over form, whereas deconstructive interpreters privilege form over content. Here, I offer a reading of Johannes Climacus’s Philosophical Fragments to illustrate how, in this case, the theology/deconstruction and form/content binaries both break down. The form of Fragments is as theological as it is deconstructive: Climacus’s kaleidoscopic quotation of scripture, and his parabolic tropes both attest to this. Similarly, the content of Fragments is as deconstructive as it is theological: the deferral of names, the madness of the moment of decision, and Climacus’s use of contradiction all unsettle any naïve theology. Ultimately, I suggest, the reason that Fragments resists the form/content and theology/deconstruction binaries is because it is a text about the incarnation—a paradigmatic combination of form and content, and a paradoxical reality that bursts apart any division between theology and deconstruction.